2013
DOI: 10.1002/hyp.9907
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire effects on extractable elements in ash from aPinus pinasterforest in Portugal

Abstract: The aim of this work is to study the effects of a wildfire on water-extractable elements in ash from a Pinus pinaster forest located in Portugal. The pH, electrical conductivity (EC), calcium (Ca 2+ ), magnesium (Mg 2+ ), sodium (Na + ), potassium (K + ), sodium and potassium adsorption ratio (SPAR), aluminium (Al 3+ ), manganese (Mn 2+ ), iron (Fe 2+ ), zinc (Zn 2+ ), sulphur (S), silica (Si) and phosphorous (P) were analysed in ash sampled from a sloped area burned in a wildfire and from litter from a contig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 110 publications
2
34
0
Order By: Relevance
“…Since hillslope soils are affected by the impacts of wildfires (Dlapa et al, 2013;Pereira et al, 2014;Dlapa et al, 2015, Tessler et al, 2015, mainly by erosion, rates, and general heat impact on the soil (Novara et al, 2013;Keesstra et al, 2014;Hedo et al, 2015;Pereira et al, 2015). Moreover, the ash and top-soil in a post-fire environment are exposed to changes introduced by the rainfall and wind (two main erosion factors).…”
Section: Introductionmentioning
confidence: 99%
“…Since hillslope soils are affected by the impacts of wildfires (Dlapa et al, 2013;Pereira et al, 2014;Dlapa et al, 2015, Tessler et al, 2015, mainly by erosion, rates, and general heat impact on the soil (Novara et al, 2013;Keesstra et al, 2014;Hedo et al, 2015;Pereira et al, 2015). Moreover, the ash and top-soil in a post-fire environment are exposed to changes introduced by the rainfall and wind (two main erosion factors).…”
Section: Introductionmentioning
confidence: 99%
“…Metals are of major importance due to their high toxicity, their long life and their tendency to bioaccumulate in aquatic systems [6]. The severity of wildfires affects the type and amount of eluted elements, while the Sodium Adsorption Ratio (SAR) is higher for intense wildfires [4]. Moreover, in Mediterranean areas, as the new hydrological year begins, rainfalls are usual during the months following the period of wildfires.…”
Section: Introductionmentioning
confidence: 99%
“…According to Pereira et al [4], Ca, S, Mg, K, and Na prevailed in soil water at an affected P. pinaster forest in Portugal. Kučerová et al [7] found high concentrations of P, N in a Pinus rotundata forest in the Czech Republic, three years after the fire.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations